Potential of oil palm leaves as an adsorbent for the removal of methylene blue from aqueous solution - Siti Fatin Raihanah, Mohd Suhaimi (2015)
Coloring effluent from industrial activities may affect environmental and human health and with this concern, many methods have been studied to decolorize such effluent including physical, chemical and biological methods. Among the methods available, adsorption process is the most commonly used to remove dyes because of its low cost, simple design and easy to perform. Adsorption onto activated carbon has been used with great success. However, its high cost sometimes tends to limit its use. Therefore, many low-cost adsorbents have been developed for dye removal such as natural materials, industrial waste and agriculture waste. So, the aim of the present work was to investigate the feasibility of oil palm leaves (OPL), a solid waste, abundantly available in Malaysia, for the adsorption of methylene blue. Batch adsorption studies were conducted to evaluate the effects of adsorbent dosage (0.25-2.0 g/L), pH (2-8), initial concentration (50-400 mg/L), and temperature (30-70 ºC). The experimental data were analyzed by the Langmuir and Freundlich isotherms, and were found to follow the Langmuir isotherm model with coefficients of correlation R2 ≥ 0.9512 indicating that the ongoing process is chemical adsorption. Pseudo-first-order and pseudo-second-order kinetics models were tested with the experimental data, and pseudo-second-order kinetics was the best for the adsorption of MB by oil palm leaves with coefficients of correlation R2 ≥ 0.998 for all initial methylene blue concentrations studied. Thermodynamic parameters such as ΔHo, ΔGo and ΔSo clearly indicated that the ongoing process is endothermic, spontaneous, and chemical in nature at 30-50oC, while at 50-70oC, the ongoing process is exothermic, spontaneous, and chemical in nature. The optimum conditions were achieved at 0.5 g/L of adsorbent dosage, pH 6, 400 mg/L initial dye concentration and 50 oC with maximum adsorption capacity of 694.6 mg/g. The adsorption of MB into the OPL was confirmed by SEM and FTIR for OPL before adsorption and after 50 min adsorption process. The results revealed that the (OPL) could be employed as a low-cost adsorbent for the removal of methylene blue from aqueous solution.